2017
DOI: 10.3171/2017.8.focus17450
|View full text |Cite
|
Sign up to set email alerts
|

Complications of invasive intracranial pressure monitoring devices in neurocritical care

Abstract: Intracranial pressure monitoring devices have become the standard of care for the management of patients with pathologies associated with intracranial hypertension. Given the importance of invasive intracranial monitoring devices in the modern neurointensive care setting, gaining a thorough understanding of the potential complications related to device placement—and misplacement—is crucial. The increased prevalence of intracranial pressure monitoring as a management tool for neurosurgical patients has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 62 publications
0
68
0
Order By: Relevance
“…24 In patients who are potential surgical candidates, the risk of haematoma expansion indicates serial CT 8-12 hours after injury. 25 For ICP monitoring, ventricular catheters are considered the gold standard in the USA. These devices permit therapeutic CSF drainage if required, although they do carry a greater infection risk.…”
Section: Non-operative Managementmentioning
confidence: 99%
“…24 In patients who are potential surgical candidates, the risk of haematoma expansion indicates serial CT 8-12 hours after injury. 25 For ICP monitoring, ventricular catheters are considered the gold standard in the USA. These devices permit therapeutic CSF drainage if required, although they do carry a greater infection risk.…”
Section: Non-operative Managementmentioning
confidence: 99%
“…ER rates of infections went from 13% to 7.7% in the ICU/OR. Although, the literature of safest environment to place an EVD is still inconsistent, some studies have concluded that the Operating Room (OR) is the optimal setting for EVD placement but nevertheless, other authors have suggested lower risk of ERIs in ICU setting [3][4][5][6][7][8][9][10][11][12][13][14][15]16]. Moreover, outcomes and complications between OR, ICU and ER have several confounders as the decision of a particular setting to place an EVD can be related to the status of the patient at initial diagnosis and requirement of an emergent procedure [1].…”
Section: Discussionmentioning
confidence: 99%
“…External ventricular drain (EVD), otherwise known as external ventriculostomy, is a neurosurgical procedure that is used for monitoring and treatment of elevated intracranial pressure (ICP) after traumatic brain injury (TBI) as well as primary hydrocephalus or secondary to subarachnoid hemorrhage (SAH), intra-parenchymal hemorrhage (IPH), intra-ventricular hemorrhage (IVH), malignancies and cerebrospinal fluid (CSF) leak [1,2]. Although EVD placement is considered a low-risk procedure, it can carry complications such as hemorrhage, obstruction of the drainage system, and the most common EVD-related infections (ERI) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, both measurement sites (intraventricular vs. parenchymal) have advantages in clinical decision making in children with severe TBI. Though the parenchymal ICP sensors have equal accuracy and probably a slightly lower complication rate compared to intraventricular ICP monitoring, the latter remains gold standard (41,42,(47)(48)(49). This may be explained by; (1) a historical perspective, (2) a less significant intercompartment pressure gradient, and (3) validation of measured ICP through an external fluid column (23).…”
Section: Comparison Of the Different Techniquesmentioning
confidence: 99%